The Implementation of Occupational Therapy to Enhance The Quality of Life of Elderly at X Nursing Home, Jakarta - Fahlevi, Reza; Zamralita; Rismiyati E Koesma (Miracle Journal Get Press, 2026)
As individuals age, they often experience physical, psychological, and social changes that can reduce their quality of life, including decreased independence, limited social participation, loneliness, and a lack of meaningful daily activities. These challenges are commonly associated with retirement, reduced social interaction, and monotonous routines, which may negatively affect emotional well-being and overall life satisfaction. This study aimed to examine the effectiveness of occupational therapy in improving the quality of life of elderly individuals. An experimental approach was applied using a one-group pretest–posttest design involving seven participants aged 66–89 years. The intervention consisted of seven group therapy sessions in which participants engaged in structured occupational activities by creating beaded brooches. Quality of life was assessed using the WHOQoL instrument before and after the intervention. The results demonstrated a substantial improvement in participants’ quality of life, with the mean WHOQoL score increasing by 36 points, from 56 to 92. Statistical analysis using a paired-samples t-test indicated that this improvement was significant, t(6) = 20.67, p < .001. These findings suggest that occupational therapy is effective in enhancing the quality of life of elderly individuals. Structured, craft-based group activities can promote active engagement, social interaction, and a sense of personal accomplishment. Practically, such low-cost interventions can be integrated into routine elderly care programs in community centers or nursing homes to reduce social isolation and support meaningful daily engagement.